Jurisprudence (Revista do Tribunal Regional Federal da 3ª Região, 2010)
FEITOS DA PRESIDÊNCIASLAT 0006035-05.2010.4.03.0000 Desembargador Federal Roberto Haddad 100/69SuExSe 0006416-13.2010.4.03.0000 Desembargador Federal Roberto Haddad 100/78SLAT 0008950-27.2010.4.03.0000 Desembargador Federal Roberto Haddad 100/82FEITOS DA VICE-PRESIDÊNCIAREsp ApelReex 0003527-35.2005.4.03.6120 Desembargador Federal André Nabarrete 100/88REsp ACr 0005637-39.2007.4.03.6119 Desembargador Federal André Nabarrete 100/91REsp HC 0018758-27.2008.4.03.0000 Desembargador Federal André Nabarrete 100/97DECISÕES MONOCRÁTICASAC 0004477-75.2004.4.03.6121 Desembargador Federal Baptista Pereira 100/101MS 0037241-71.2009.4.03.0000 Desembargador Federal Newton De Lucca 100/108CC 0037305-81.2009.4.03.0000 Desembargadora Federal Diva Malerbi 100/111CC 0038148-46.2009.4.03.0000 Desembargadora Federal Marisa Santos 100/115AI 0042463-20.2009.4.03.0000 Desembargador Federal Antonio Cedenho 100/121MS 0044715-93.2009.4.03.0000 Desembargador Federal Walter do Amaral 100/124MS 0001610-32.2010.4.03.0000 Desembargador Federal André Nabarrete 100/127AI 0004388-72.2010.4.03.0000 Juiz Federal Roberto Lemos 100/142AR 0007555-97.2010.4.03.0000 Desembargadora Federal Marli Ferreira 100/149JURISPRUDÊNCIAAGRAVOAg AC 0039282-89.2006.4.03.9999 Desembargador Federal Nelson Bernardes 100/162Ag AC 0012638-43.2008.4.03.6183 Desembargador Federal Sérgio Nascimento 100/166Ag AI 0023733-92.2008.4.03.0000 Juiz Federal Leonel Ferreira 100/170Ag AC 0056222-61.2008.4.03.9999 Desembargadora Federal Anna Maria Pimentel 100/177Ag AI 0036927-28.2009.4.03.0000 Desembargador Federal André Nekatschalow 100/193AGRAVO DE INSTRUMENTOAI 0038148-27.2001.4.03.0000 Desembargador Federal Lazarano Neto 100/200AI 0029909-29.2004.4.03.0000 Desembargadora Federal Consuelo Yoshida 100/206AI 0036458-55.2004.4.03.0000 Desembargador Federal Márcio Moraes 100/212AI 0103318-33.2007.4.03.0000 Desembargadora Federal Vesna Kolmar 100/216AI 0031195-66.2009.4.03.0000 Desembargadora Federal Therezinha Cazerta 100/223AI 0033259-49.2009.4.03.0000 Desembargador Federal Nery Júnior 100/237AI 0043559-70.2009.4.03.0000 Juíza Federal Noemi Martins 100/241APELAÇÃO CÍVELAC 93.03.066181-8 Juiz Federal Jairo Pinto 100/250AC 94.03.079746-0 Juiz Federal Marcelo Duarte 100/259AC 95.03.037141-4 Juiz Federal João Consolim 100/270AC 0002229-48.1999.4.03.6110 Desembargadora Federal Vera Jucovsky 100/278AC 0004024-95.1999.4.03.6108 Juiz Federal Silva Neto 100/292AC 0004869-54.1999.4.03.6100 Juíza Federal Monica Nobre 100/299ApelReex 0000358-43.2000.4.03.6111 Juiz Federal Hélio Nogueira 100/312AC 0001965-36.2000.4.03.6000 Juiz Federal Rubens Calixto 100/322AC 0032150-79.2000.4.03.0399 Desembargador Federal Fábio Prieto 100/328AC 0001420-78.2001.4.03.6113 Desembargadora Federal Regina Costa 100/343ApelReex 0005219-59.2001.4.03.6104 Desembargador Federal Mairan Maia 100/359ApelReex 0014309-06.2001.4.03.6100 Desembargador Federal Nelton dos Santos 100/365AC 0039272-12.2001.4.03.0399 Juiz Federal Roberto Jeuken 100/374AC 0004241-84.2003.4.03.6113 Juiz Federal Souza Ribeiro 100/387AC 0032420-98.2003.4.03.0399 Juiz Federal Alexandre Sormani 100/401AC 0004004-89.2004.4.03.6121 Desembargador Federal Roberto Haddad 100/409AMS 0022694-35.2004.4.03.6100 Desembargador Federal Carlos Muta 100/414AMS 0024961-77.2004.4.03.6100 Desembargadora Federal Cecília Marcondes 100/428AC 0026046-41.2004.4.03.9999 Desembargadora Federal Marianina Galante 100/435AC 0018751-07.2005.4.03.0399 Desembargador Federal Cotrim Guimarães 100/440AMS 0007662-36.2008.4.03.6104 Desembargadora Federal Salette Nascimento 100/461APELAÇÃO CRIMINALACr 0002558-56.2005.4.03.6108 Juiz Federal Márcio Mesquita 100/469CAUTELAR INOMINADACauInom 0024414-43.2000.4.03.0000 Juíza Federal Giselle França 100/481CONFLITO DE COMPETÊNCIACC 0085517-75.2005.4.03.0000 Desembargadora Federal Suzana Camargo 100/490CC 0004697-30.2009.4.03.0000 Desembargadora Federal Ramza Tartuce 100/497EMBARGOS DE DECLARAÇÃOEDcl AC 0017893-42.2005.4.03.6100 Desembargador Federal Henrique Herkenhoff 100/507EDcl HC 0020764-75.2006.4.03.0000 Juiz Federal Ricardo China 100/511EMBARGOS INFRINGENTESEI 0039442-51.2005.4.03.9999 Desembargadora Federal Eva Regina 100/516“HABEAS CORPUS”HC 0028641-61.2009.4.03.0000 Desembargador Federal Luiz Stefanini 100/532MANDADO DE SEGURANÇAMS 0037252-13.2003.4.03.0000 Desembargador Federal Johonsom di Salvo 100/538RECURSO EM SENTIDO ESTRITORSE 0001631-79.2004.4.03.6123 Desembargador Federal Peixoto Junior 100/551RSE 0008609-29.2004.4.03.6105 Desembargadora Federal Cecilia Mello 100/559REEXAME NECESSÁRIO CÍVELREOMS 97.03.007206-2 Juiz Federal Valdeci dos Santos 100/570REOMS 0004684-10.1999.4.03.6102 Desembargadora Federal Leide Polo 100/578REOMS 0003867-82.2004.4.03.6000 Desembargadora Federal Alda Basto 100/582